Online social networking: reflections on social relations amongst a group of students, University of the Free State, Bloemfontein - Sele, Sello Jan (University of the Free State, 2018)
Online social networking (OSN) as an activity carried out through social network sites (SNS) is without a doubt, a predominant interaction mechanism which best characterises the 21st century. The advent of SNS has acutely penetrated almost all areas of our social and professional lives. Thus, SNS are woven inextricably into the fabric of individuals‘ everyday lives, most especially the lives of students. This study therefore aims to broaden an understanding on how the students of the University of the Free State (UFS), Bloemfontein campus perceive, feel, experience, respond to, and make sense of the interactions and social relations via OSN in their everyday lives. Various sociological theories are applied to make sense of the participants‘ lived experiences within the context of OSN. Three theoretical frameworks are used in this study: phenomenology, existentialism and reflexive sociology. Phenomenology assists in looking at how the target population makes sense of the OSN activities both on subjective and intersubjective levels. This theoretical framework is also concerned with how individuals construct reality within their lifeworlds — the OSN realm in this case. When taking a look at existentialism, the emphasis is more on the issues associated with the role of affect and a human‘s sense of self in society. This theory sheds light on how emotions are expressed through SNS and how the users assert their individual identities in these virtual spaces. Moreover, reflexive sociology is the theory which seeks to bring together the aspects of objective and subjective approaches in studying social reality. This theory rejects the sociological paradigms which overemphasise the importance of either the objective or subjective dimension of phenomena while the other dimension is downplayed. Hence, this study explores both the objective and subjective aspects of OSN in order to broaden an understanding thereof. This study assumes a mixed methods approach to social inquiry — both quantitative and qualitative approaches were used to collect, analyse and present the data. Although this research adopts a mixed methods approach, it is predominantly interpretive. Aspects of a quantitative design serves two main functions in this study: firstly, this method was used as a means to lead to appropriate recruitment of the sample for one-on-one interviews. Secondly, it is used to back-up the qualitative data. A quantitative survey as the first phase of data collection was conducted among 100 (50 respondents for each gender) students of the UFS to which closed-ended questionnaires were administered. In-depth interviews as the second phase of data collection were conducted on 6 participants. Audio-recording devices were used as data collection instruments for participants‘ narratives. Lastly, a focus group was conducted on 4 participants selected from those who participated in the individual interviews. Before the data were collected, approval letters from the UFS Ethics Committee within the Faculty of Humanities and relevant university authorities were obtained. The findings presented in this study are based on both quantitative (chapter 4) and qualitative chapter 5) analyses. However, more attention is dedicated to the qualitative aspect of this study as it is considered to be the cornerstone of this research. Amongst the most important variables measured, as presented in chapter 4, is the time spent on SNS by student respondents. the results indicate that the respondents spend a considerable amount of time online. The statistical data also reveal that the most preferred SNS by the respondents are WhatsApp and Facebook ― presumably the sites where students spend a lot of time. When looking at the qualitative findings, a common sentiment amongst the participants regarding their involvement in SNS is that they cannot imagine their lives without these online platforms. They believe that OSN is the most effective tool for social interaction in their lifetime. When coming to the issue of identity, most participants claim that the identities they portray online are different from the ones they portray in real life. Thus SNS allow them to be autonomous over their projected identities. Although participants interact and construct relations through open SNS such as Facebook and Twitter, some of them strongly disregard interacting with strangers they come across in those SNS. Their disapproval of interacting with strangers stems from past personal experiences (undesirable) with strangers. Moreover, the participants also express a great deal of knowledge and experience regarding the ramifications that come with SNS. These repercussions are related to identity theft, defamation of character, hackings and online victimisation.
Dissertation (M.Soc.Sc. (Sociology))--University of the Free State, 2017
Keywords: Phenomenology; Existential phenomenology; Reflexive sociology; Lifeworld; Mixed methods approach; Online social networking (OSN); Social network sites (SNS); Social interaction; Social support; Identity